Penggunaan Sonkeigo (Kata Hormat) Bahasa Jepang dalam Informed Consent dengan Metode Drill : Use of Sonkeigo (Honors) in Japanese in Informed Consent with Drill Method - I Gusti Agung Galuh Wismadewi; Putu Rusanti; Ni Wayan Novi Suryati; Kadek Maya Cyntia Dewi (ITScience (Information Technology and Science), 2024)
This study aims to determine the teaching strategies used by Japanese language lecturers. This study was designed as a qualitative descriptive study. Conjugation in Japanese is diverse, but the author only discusses the Drill learning model to facilitate mastery of Japanese nursing vocabulary according to the research conducted by the author. From the information obtained, 69.1% of students' responses stated that they agreed that they enjoyed learning using the Drill method. This shows that the Drill learning method can attract students' interest in learning to speak Japanese. With the drill method, students are more motivated to remember nursing vocabulary and expressions spoken repeatedly, which means they are motivated to speak because speaking in Japanese is not boring. Students can also exchange ideas with their friends if they find words that are difficult. One of the benefits of this method is that learning can be done anywhere and anytime. The questionnaire results showed that 74.5% of students strongly agreed with using the Drill method. The drill method in learning Japanese, especially in speaking skills (kaiwa), can help because students can work together if they have difficulty speaking Japanese. As many as 69.1% of students agreed they enjoyed learning using the Drill method. The obstacles students face can be overcome because when teaching material about nursing vocabulary and pronunciation in Japanese, the lecturer uses the Drill method to make nursing vocabulary easy for students to remember.